2005
DOI: 10.1097/01.ju.0000158156.80315.fe
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hospital Volume on Cancer Control After Radical Prostatectomy

Abstract: Patients treated at lower volume institutions are at increased risk of initiation of subsequent adjuvant therapy with radiation therapy, medical hormone ablation or orchiectomy. Noted differences in cancer control provide additional evidence regarding issues surrounding the debate over surgical volume standards for the surgical treatment of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 18 publications
3
51
0
Order By: Relevance
“…Various studies from the USA have examined such volume-outcome relationships using a Medicare database [2] . The patient demographics of this study are similar to previous population-based studies [9,10] . Though there was a great difference in the total number of radical procedures and volume thresholds in the present study and others, equal division of patients into 4 groups (quartiles) may nullify the cut-off volume threshold bias.…”
Section: Discussionsupporting
confidence: 70%
“…Various studies from the USA have examined such volume-outcome relationships using a Medicare database [2] . The patient demographics of this study are similar to previous population-based studies [9,10] . Though there was a great difference in the total number of radical procedures and volume thresholds in the present study and others, equal division of patients into 4 groups (quartiles) may nullify the cut-off volume threshold bias.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, registries can provide information on the quality of clinical care. In this context, studies based on several of these data sources have demonstrated that better outcomes might be achieved in high-volume hospitals and/or with more experienced surgeons [21,76]. The evaluation of large cohorts with follow-up data on cancer control has an important role in assessment of the safety and efficacy of PCa treatments [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94].…”
Section: 4mentioning
confidence: 99%
“…[3][4][5][6] Furthermore, ongoing controversy over many aspects of the management of prostate cancer 7,8 has led to regional and institutional variations in treatment 7,[9][10][11][12][13][14] with some evidence that these variations can lead to differences in outcome. 4,15,16 The timely evaluation of quality of care in the surgical treatment of prostate cancer has become a priority, although there is little known about which aspects of quality should be examined. 17 Quality of care research evaluates the ''degree to which health services for individuals and populations increase the likelihood of desired health outcomes and are consistent with current professional knowledge.''…”
mentioning
confidence: 99%